Management of desmoid tumours: A nationwide survey of labelled reference centre networks in France. (May 2016) - Penel, Nicolas; Coindre, Jean-Michel; Bonvalot, Sylvie; Italiano, Antoine; Neuville, Agnès; Le Cesne, Axel; Terrier, Philippe; Ray-Coquard, Isabelle; Ranchere-Vince, Dominique; Robin, Yves-Marie; Isambert, Nicolas; Ferron, Gwennaël; et al.
Abstract: Purpose: The optimal management of rare tumours (i.e. from accurate diagnosis to management in reference centres) is a public health challenge. In 2009, the French National Cancer Institute (INCa) identified and financially supported the two expert networks for pathological and clinical diagnosis and management of soft tissue tumours. Methods: The activities of both networks were prospectively collected using a nationwide database (rreps.org ). Data describing the diagnosis management of 863 successive cases of desmoids tumours (DT) were prospectively collected from 2010 to 2013 and analysed. Results: The number of confirmed DT constantly improved from January 2010 to December 2013 (from 173 to 273 cases per year); the expected incidence ranged from 132 to 330 cases/year. The rate of cases diagnosed with core-needle biopsies and CTNNB1 mutational status analysis increased from 30.6 to 40.7% and from 87.8 to 94.1%, respectively. The mean delay for pathological diagnosis confirmation constantly decreased from 107 to 47 d. Among the 846 adult patients, 414 (48.9%) patients were treated by reference centres. The rate of patients managed by reference centres constantly increased with time from 36.9 to 49.5% since 2010. The median management time of the referral centres constantly decreased from 440 to 67 d. Conclusion: The two expert networks worked synergistically and improved diagnosis modalities of rare desmoid tumours at a national level. The impact of management by expert networks on the outcome will be prospectively analysed in the future. Highlights: Two experts networks for management of connective tissue tumours have been implemented in France. This is associated with increase of confirmed incident cases of desmoid tumours. This is associated with significant decrease in delay for diagnosis confirmation. This is associated with significant decrease in management delay of desmoid tumours. This is associated with analysis of CTNNB1 somatic mutation in 90% of cases.